Missing the forest for the trees: Scientometric analysis of "Sustainable versus regenerative" tourism (1966-2023) - Umer Zaman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
The ongoing global debate over sustainable versus regenerative tourism underscores the complex interplay between intentions and outcomes in responsible travel. Hence, the purpose of the study is to; (i) summarize sustainable and regenerative tourism research from 1966 through 2023; (ii) take into account the general context of research from the viewpoint of journal papers that have been published, in addition to co-occurrences of keywords, cluster analysis, visual mapping, and document co-citations (iii) identify the research gap in the sustainable versus regenerative tourism research, as well as emphasis on the utmost knowledge domains, and (iv) suggest future research areas in sustainable and regenerative tourism. To accomplish this objective, the study utilized the scientometric analysis approach, which involves visual mapping and reviewing the specific knowledge domain, through analytical tools, including VOS-viewer and Cite-Space. By applying the proximity investigation procedure, published studies underwent relational examination using the 'concept matrix' and cluster of co-existing terms. 3850 full-text research papers on sustainable and regenerative tourism published in Web of Science between 1966 and 2023, including 7052 researchers from 132 countries were examined. The present study findings highlight an up-to-date scientometric analysis from 1966 through 2023, as it identifies prominent researchers, mainstream tourism journals, publication trends, leading countries, researched areas, funding institutions and affiliations within the area of sustainable and regenerative tourism. The findings shed light on sustainable and regenerative tourism trends, challenges, and key players to inform future research and policy.
Keywords: 330; Sustainable tourism; sustainable travel; regenerative tourism; regenerative travel; green tourism; scientometric analysis